Air pollution and emergency hospital admissions for cardiovascular diseases in Valencia, Spain. Issue 1 (1st January 2001) - Ballester, F; Tenías, J M; Pérez-Hoyos, S
Abstract : STUDY OBJECTIVE: To estimate the short-term association between air pollution levels and emergency hospital admissions for cardiovascular diseases in Valencia, within 1994–1996 period. DESIGN: Daily levels of air pollution and emergency admissions for cardiovascular diseases were related to using an ecological time series design. The number of admissions was obtained from the hospital records database. Selected groups of causes were all cardiovascular diseases, heart admissions, and admissions for cerebrovascular diseases. The number of admissions for digestive diseases was used as control. Pollutants were black smoke, sulphur dioxide (SO2 ), nitrogen dioxide (NO2 ), carbon monoxide (CO) and ozone (O3 ). Magnitude of association was estimated by Poisson autoregresive regression. Estimations were calculated according the hottest (May to October) and the coldest (November to April) periods. SETTING: City of Valencia, Spain, about 750 000 inhabitants. PARTICIPANTS: People being admitted to the two major hospitals in the city, with a catchment area of nearly 400 000 inhabitants. MAIN RESULTS: For the whole period, a significant association for SO2 -24 h was found so a rise in its levels of 10 μg/m 3 was associated with an increment of 3% (95%CI 0.4 to 5.7%) in the expected number of cardiovascular admissions. A significant association for black smoke, SO2 -24 h, SO2 -1 h, and CO-1 h was found in the hottest semester. All these associations were verified with a lag of two days. The estimates of the associations for particles, SO2, and CO were affected by the inclusion of the other pollutants in their models. NO2 was independently associated with cerebrovascular admissions. There were no significant associations between air pollution and admissions for digestive diseases. CONCLUSIONS: Current levels of air pollution and emergency cardiovascular admissions are significantly related in Valencia.